Assessment of Natural Radioactivity Levels and Radiation Hazards in Agricultural and Virgin Soil in the State of Kedah, North of Malaysia - Ghazwa Alzubaidi; Fauziah B. S. Hamid; I. Abdul Rahman (The Scientific World Journal)
The activity concentrations of naturally occurring radionuclides 226Ra, 232Th, and 40K were determined in 30 agricultural and virgin soil samples randomly collected from Kedah, north of Malaysia, at a fertile soil depth of 0–30 cm. Gamma-ray spectrometry was applied using high-purity germanium (HPGe) gamma-ray detector and a PC-based MCA. The mean radioactivity concentrations of 226Ra, 232Th, and 40K were found to be 102.08 ± 3.96, 133.96 ± 2.92, and 325.87 ± 9.83 Bq kg−1, respectively, in agricultural soils and 65.24 ± 2.00, 83.39 ± 2.27, and 136.98 ± 9.76 Bq kg−1, respectively, in virgin soils. The radioactivity concentrations in agricultural soils are higher than those in virgin soils and compared with those reported in other countries. The mean values of radium equivalent activity (Raeq), absorbed dose rates D (nGy h−1), annual effective dose equivalent, and external hazard index (Hex) are 458.785 Bq kg−1, 141.62 nGy h−1, and 0.169 mSv y−1, respectively, in agricultural soils and 214.293 Bq kg−1, 87.47 nGy h−1, and 0.106 mSv y−1, respectively, in virgin soils, with average Hex of 0.525. Results were discussed and compared with those reported in similar studies and with internationally recommended values.